الفكر السياسي والنظرية السياسية: دراسة مقارنة - عبدالكريم، أسعد عبدالوهاب Abdulkarim, Asaad Abdulwahab (جامعة تكريت - كلية الآداب, 2016)
تعد هذه الدراسات بمثابة الجذور الأساسية التي تبنى عليها معظم الأعمال السياسية، من الفرد والمجتمع والدولة، وما يتفرع منها من مذاهب وأيدلوجيات وأحزاب وحكومات وأشكال للدول، وتبنى عليها العلاقات الدولية والدبلوماسية، ويتمكن الإنسان من تثبيت وتضمين حقوقه أمام الدولة المجتمع والمنظمات الدولية، ومنها أيضا تنطلق الأفكار لمعالجة النزاعات والمشاكل بين الجماعات والدول. تنطلق الأهمية من الحاجة إلى دراسة الفكر السياسي أو النظرية السياسية، وتحديد المفاهيم العامة والمفردات الخاصة لكل منهما. إذ لا يمكن لدارس العلوم السياسية أن يتجاهل الفكر السياسي والنظرية السياسية. ومن فرضية مفادها إن الفكر السياسي والنظرية السياسية كلاهما جزء لا يتجزأ في عملية التحليل السياسي للظواهر السياسية. ورغم أن الفكر السياسي يتقدم على النظرية في عدة أوجه ألا أن النظرية السياسية نتميز بعدة خصائص. وتوصل البحث إلى مجموعة من النتائج منها: • أن الفكر سابق على النظرية. • أن الفكر السياسي يمتلك نظرية سياسية بالضرورة، والعكس صحيح. • وأن النظرية السياسية تصطبغ بالعلمية. • تعتمد النظرية السياسية في دراستها على الظواهر والفرضيات للوصول إلى قوانين عامة أو مسلمات يمكن من خلالها الوصول النتائج محدد. • أن الفكر السياسي يتسم بالعمومية في الطرح.
This study serves as basic roots upon which most of the political business, from the individual and the society and the state, and the ramifications of which doctrines and ideologies and parties, governments and forms countries. This study adopted by the International Relations and Diplomacy, and able man to install and include their rights in front of the state community and international organizations, which also kicks off ideas to address problems and conflicts between groups and nations. It kicks off the importance of the need to study the political ideology or political theory, and determine the general concepts and vocabulary for each. It cannot for the student of political science that ignores political thought and political theory. On the premise, that political thought and political theory both are integral to the process of political analysis of political phenomena part. Although the political ideology ahead of theory in several ways, but the political theory is characterized by several properties. The research found a set of results including: • The former thought the theory. • The political thought has necessarily political theory, and vice versa. • Political theory in the study on the phenomena and assumptions to reach the general laws or axioms from which to reach specific results. • The political thought generalized in the offering.
Keywords: الفكر السياسي -- النظرية السياسية -- التحليل السياسي